Digitalization of TVET management in Malaysia: A shift towards electronic certificates - Nurul Amin Badrul; Saidi Zain; Azah Mahani Mohd (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2025)
In an era marked by rapid technological advancements and increasing demands for efficient and secure document management, transforming paper-based certificates into electronic certificates has emerged as a critical undertaking for the TVET sector. The conversion of physical certificates to digital formats involves digitising their content, implementing verification mechanisms, and securely storing them in electronic repositories. This paradigm shift reduces the environmental footprint associated with paper documentation and enhances accessibility, security, and efficiency in certificate management. Moreover, digital certificates enable the integration of advanced technologies, such as blockchain, to ensure the document's security and authenticity. The study reveals that electronic certification systems implemented by various institutions commonly incorporate features such as QR-code verification, blockchain technology, Public Key Infrastructure (PKI), cloud-based storage, and online validation mechanisms to enhance authenticity, security, and accessibility. Furthermore, key stakeholders across various agencies strongly support the implementation of electronic certificates due to their enhanced security features, reduced administrative burden, and improved operational efficiency. A qualitative approach was performed through semi-structured interviews with key stakeholders. The study reveals that key stakeholders across various agencies strongly support the idea of electronic certificates. Institutions and organizations are embracing this transformation due to the enhanced security features, reduced administrative burdens, and increased efficiency of electronic certificates. Furthermore, the environmental benefits of reduced paper usage align with the National Green Technology Policy and are gaining traction among stakeholders. The findings improve understanding regarding the digitization of TVET certification towards electronic certificates in line with technological advancement.